Optimizing Eco-Efficiency of green Infrastructure: A comparative study of woody plant species Utilizing SWMM-HYDRUS model and Analytic Hierarchy process - Bei Zhang; Zheng Liang; Lidong Zhao; Letong Ma; Shouhua Zhang; Taolve Gao; Liang Chen (Ecological Indicators)
Urban greening and effective control of non-point source pollution are critical objectives that can be achieved through the implementation of green infrastructures (GIs) for sustainable rainwater management. To explain the overarching patterns of GIs dominated by representative woody plants and their influence on urban environmental conditions, a coupled HYDRUS-1D and SWMM model (NSE ≥ 0.64 and R2 ≥ 0.71) was developed to simulate the hydrological response of various root systems employed in woody plant cultivation in urban areas. The analysis of surface runoff regulation revealed that the average reduction rate of runoff in GIs increased from 57 % to 73 % as the planting area expanded (5 % to 25 %) during a design rainfall event with a 2-year recurrence interval. Notably, the GI consisting of Sophora japonica, characterized by tap roots, exhibited a superior runoff reduction effect compared to the GI comprising Malus baccata, which possesses fibrous roots, and the control group without vegetation. To comprehensively evaluate and optimize the rainwater utilization technology, an analytic hierarchy process was employed to construct a comprehensive benefit assessment system, including environmental, economic, and societal aspects, for woody plants with varying planting areas in the study region. The analysis revealed that planting density of 15 % for Malus baccata maximizes comprehensive benefit values, positioning it as the optimal choice for woody plant cultivation within the study area. This research not only underscores the ecological benefits of carefully selected woody plants in urban GIs but also provides valuable insights for urban planners aiming to enhance ecological resilience and sustainability.